A study on psychological stress assessment of higher educational institution’s students based on computer data mining technology - Chen, Shaohong (Frontiers in Psychology, 2023)
Safety begins in the human mind, and the individual's need for psychological safety is the most fundamental need. This fundamental need takes psychological safety as the starting point for the gradual formation of a connection with the outside world. Graduates are the backbone of China's economic development, and their healthy development is of great significance to the sustainable development of China’s economy and society. Excessive psychological pressure may bring pain to students in physical and psychological aspects, and even lead to suicide. If students with abnormal psychological pressure can be found in time; the school can provide help and intervention in time to relieve psychological pressure. This paper uses pressure sensor technology for data collection and data mining techniques for data analysis to assess and predict the psychological stress level of Higher Educational Institutions (HEIs) students. The results show that this method can accurately and objectively evaluate the psychological stress of the students, and the evaluation results of students' psychological stress are stable, which can provide students with psychological stress assessment services. It implies that HEI’s policymakers should consider these techniques to assess the psychological stress of the students proactively.